Single-crystal lithium-rich manganese-based positive electrode material, preparation method thereof and lithium ion battery

CN122930876APending Publication Date: 2026-10-16SHANGHAI XUANYI NEW ENERGY DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611187138.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]本申请的主要目的在于提供一种单晶富锂锰基正极材料及其制备方法和应用,以解决现有技术中的锂离子电池首次库伦效率较低、直流内阻增长明显以及循环寿命差的问题

Benefits of technology

[0040]This application provides a single-crystal lithium-rich manganese-based cathode material. The coating layer formed on the surface of the single-crystal lithium-rich manganese-based particles can effectively isolate the direct contact between the electrolyte and the single-crystal lithium-rich manganese-based particles under high voltage, further effectively suppressing interfacial side reactions and transition metal dissolution. Furthermore, by controlling the thickness of the coating layer and the content of each component in the lithium-rich manganese-based cathode material, the DC resistance (DCR) of the battery during cycling is reduced. At the same time, introducing at least one stable doping element of Zr, Al, W, Mg, Ti, V, and Mo into the lithium-rich manganese-based cathode material and adding excess lithium for lithium replenishment can effectively reduce lithium loss. Meanwhile, the control of x, y, z and composition can improve the coulombic efficiency during the first charge and discharge process of the lithium-ion battery and the cycle stability of the lithium-ion battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930876A_ABST
    Figure CN122930876A_ABST
Patent Text Reader

Abstract

The application provides a single-crystal lithium-rich manganese-based positive electrode material, which comprises single-crystal lithium-rich manganese-based particles and a coating layer coated on the surface of the single-crystal lithium-rich manganese-based particles, wherein the coating layer is a lithium-containing inorganic substance, the thickness of the coating layer is 5-50 nm, the coating layer can effectively isolate direct contact between electrolyte and the single-crystal lithium-rich manganese-based particles under high voltage, effectively inhibit the interface side reaction and transition metal dissolution, and the thickness of the coating layer and the content of each component in the lithium-rich manganese-based positive electrode material are controlled, so that the direct current resistance (DCR) of the battery in the cycle process is reduced; at least one stable doping element of Zr, Al, W, Mg, Ti, V and Mo is introduced into the lithium-rich manganese-based positive electrode material, and excess lithium is added for lithium supplement, which can effectively reduce lithium loss, at the same time, x, y, z and components are controlled, so that the coulombic efficiency in the first charge-discharge process of the lithium ion battery and the cycle stability of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of lithium-ion batteries, and more specifically, to a single-crystal lithium-rich manganese-based cathode material, its preparation method, and a lithium-ion battery. Background Technology

[0002] Lithium-rich manganese-based cathode material xLi2Mn2O3 2 (M = Ni, Co, Mn, etc.) is considered one of the most promising cathode materials for next-generation high-energy-density lithium-ion batteries due to its advantages such as high specific capacity (>250 mAh / g), high operating voltage, and low cost. However, this type of material still faces many challenges in practical applications.

[0003] First, in the first charging process of traditional lithium-rich manganese-based materials, the Li2MnO3 component is activated, accompanied by the irreversible precipitation of lattice oxygen and the extraction of lithium ions, resulting in a low initial coulombic efficiency (usually below 85%) and a large loss of active lithium.

[0004] Secondly, during the high-voltage cycling process of 4.3V~4.5V, the side reactions between the material and the electrolyte are intense, which can easily lead to the thickening of the electrode / electrolyte interface film, causing a significant increase in DC internal resistance (DCR), accompanied by serious gas generation problems at high temperatures, which severely deteriorates the cycle life and safety performance of the battery.

[0005] Furthermore, traditional secondary spherical lithium-rich manganese-based material particles are formed by the agglomeration of primary nanoparticles, which are prone to intergranular cracking during cycling, further aggravating side reactions and performance degradation.

[0006] In view of the above, this application is hereby submitted. Summary of the Invention

[0007] The main objective of this application is to provide a single-crystal lithium-rich manganese-based cathode material, its preparation method, and its application, in order to solve the problems of low initial coulombic efficiency, significant increase in DC internal resistance, and poor cycle life in existing lithium-ion batteries.

[0008] To achieve the above objectives, according to the first aspect of this application, a single-crystal lithium-rich manganese-based cathode material is provided. The single-crystal lithium-rich manganese-based cathode material includes single-crystal lithium-rich manganese-based particles and a coating layer covering the surface of the single-crystal lithium-rich manganese-based particles. The coating layer is made of a lithium-containing inorganic material, and the thickness of the coating layer is 5-50 nm. The general formula of the single-crystal lithium-rich manganese-based cathode material is Li. 1+x Ni a Co b Mn c M y Q zO2, where a+b+c=1, 0.2≤a≤0.5, 0≤b≤0.1, 0.08≤x≤0.28, 0<y≤0.03, 0<z≤0.04, element M is a dopant element and is doped in the coating layer, M is selected from at least one of F, P, and B, and Q is selected from at least one of Zr, Al, W, Mg, Ti, V, and Mo.

[0009] Furthermore, the particle size of the single-crystal lithium-rich manganese-based cathode material is 2~6μm.

[0010] Furthermore, in the general formula of single-crystal lithium-rich manganese-based cathode materials, 0.1≤x≤0.25, 0<y≤0.02, and 0<z≤0.02.

[0011] Furthermore, Q is selected from at least one of Zr, Al, W, Ti, and V.

[0012] Furthermore, the thickness of the coating layer is 5~20nm.

[0013] Furthermore, the lithium-containing inorganic material contains lithium and also contains at least one selected from ZrO2, Al2O3, WO3, MgO, TiO2, V2O5, MoO3, AlF3, TiF2, ZrF2, MgF2, AlPO4, and AlBO3.

[0014] Furthermore, the chemical formula of the single-crystal lithium-rich manganese-based particles is selected from Li 1.2 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.08 Ni 0.2 Co 0.1 Mn 0.7 F 0.02 Al 0.005 O2, Li 1.25 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.1 Ni 0.4 Co 0.08 Mn 0.5 2F 0.01 Al 0.01 O2, Li 1.28 Ni 0.5 Co 0.05 Mn 0.45 F 0.005 Al 0.02 At least one of O2.

[0015] To achieve the above objectives, according to a second aspect of this application, a method for preparing a single-crystal lithium-rich manganese-based cathode material is provided, the method comprising:

[0016] Step S1: Prepare the precursor by mixing nickel source, cobalt source, manganese source and dopant element Q source to form the precursor;

[0017] Step S2: The precursor and lithium source are mixed in stoichiometric ratio to obtain a mixture, and the mixture is subjected to a first sintering to obtain a first sintered product.

[0018] Step S3: The first sintered product is mixed with the dopant element M source for a second sintering, so that the dopant element M is doped on the surface of the first sintered product to form a lithium-containing inorganic coating layer, and the second sintered product is obtained; the second sintered product is crushed and sieved to obtain a single crystal lithium-rich manganese-based cathode material.

[0019] Furthermore, the method for preparing the precursor includes:

[0020] Step S11: Mix the nickel source, cobalt source, manganese source and the dopant element Q source to obtain a mixed metal salt;

[0021] Step S12: The precursor is prepared by mixing the mixed metal salt, precipitant and complexing agent.

[0022] Furthermore, the temperature of the first sintering is 850~1000℃, the time of the first sintering is 8~20h, and the heating rate of the first sintering is 2~10℃ / min.

[0023] Furthermore, the heating rate for the first sintering is 2~5℃ / min.

[0024] Furthermore, the temperature of the second sintering is 300~700℃, the time of the second sintering is 4~10h, and the heating rate of the second sintering is 2~10℃ / min.

[0025] Furthermore, the first sintering is carried out under a protective atmosphere, which is selected from at least one of nitrogen, argon, and helium.

[0026] Furthermore, the second sintering is carried out in a mixed atmosphere, which is a mixture of inert gas and reducing gas.

[0027] Furthermore, the inert gas is selected from at least one of helium and argon, and the reducing gas is selected from at least one of hydrogen, carbon monoxide, and ammonia, with the volume of the reducing gas accounting for 3% to 5% of the volume of the mixed atmosphere.

[0028] Further, in step S2, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, or lithium nitrate.

[0029] Furthermore, in step S3, the dopant element M source is selected from at least one of lithium fluoride, ammonium dihydrogen phosphate, boron oxide, aluminum trifluoride, lithium manganese borate, and lithium vanadium phosphate.

[0030] Furthermore, in step S11, the nickel source is a soluble nickel salt, which is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate.

[0031] Furthermore, the cobalt source is a soluble cobalt salt, which is selected from at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate.

[0032] Furthermore, the manganese source is a soluble manganese salt, which is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate.

[0033] Furthermore, the source of the dopant element Q is at least one of sulfate, nitrate, chloride, or oxide containing the dopant element Q.

[0034] Furthermore, step S12 also includes mixing a mixed metal salt solution, a precipitant, and a complexing agent to carry out a co-precipitation reaction, followed by drying to obtain a precursor.

[0035] Furthermore, the pH value of the coprecipitation reaction is 10.5~12.

[0036] Furthermore, the temperature for the coprecipitation reaction is 40~70℃.

[0037] Furthermore, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate.

[0038] Furthermore, the complexing agent is selected from at least one of ammonia, citric acid, and ethylenediaminetetraacetic acid.

[0039] According to a third aspect of this application, a lithium-ion battery is provided, the lithium-ion battery including a positive electrode sheet, the positive electrode sheet including a monocrystalline lithium-rich manganese-based positive electrode material provided according to the first aspect of this application or a monocrystalline lithium-rich manganese-based positive electrode material prepared according to the preparation method provided according to the second aspect of this application.

[0040] This application provides a single-crystal lithium-rich manganese-based cathode material. The coating layer formed on the surface of the single-crystal lithium-rich manganese-based particles can effectively isolate the direct contact between the electrolyte and the single-crystal lithium-rich manganese-based particles under high voltage, further effectively suppressing interfacial side reactions and transition metal dissolution. Furthermore, by controlling the thickness of the coating layer and the content of each component in the lithium-rich manganese-based cathode material, the DC resistance (DCR) of the battery during cycling is reduced. At the same time, introducing at least one stable doping element of Zr, Al, W, Mg, Ti, V, and Mo into the lithium-rich manganese-based cathode material and adding excess lithium for lithium replenishment can effectively reduce lithium loss. Meanwhile, the control of x, y, z and composition can improve the coulombic efficiency during the first charge and discharge process of the lithium-ion battery and the cycle stability of the lithium-ion battery. Attached Figure Description

[0041] The accompanying drawings, which form part of this application, are used to provide a further understanding of this application. The illustrative embodiments and descriptions of this application are used to explain this application and do not constitute an undue limitation of this application. In the drawings:

[0042] Figure 1 A schematic SEM image of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application is shown.

[0043] Figure 2 The charge-discharge curves of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application are shown at 0.1C and 1C rates.

[0044] Figure 3 The cycling retention curve of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application after 500 cycles at 1C rate is shown. Detailed Implementation

[0045] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present application will now be described in detail with reference to the embodiments.

[0046] As described in the background section of this application, existing lithium-ion batteries suffer from low initial coulombic efficiency, significant increase in DC internal resistance, and poor cycle life. To address these issues, this application provides a single-crystal lithium-rich manganese-based cathode material, its preparation method, and a lithium-ion battery thereof.

[0047] In a first typical embodiment of this application, a single-crystal lithium-rich manganese-based cathode material is provided. The single-crystal lithium-rich manganese-based cathode material includes single-crystal lithium-rich manganese-based particles and a coating layer covering the surface of the single-crystal lithium-rich manganese-based particles. The coating layer is made of lithium-containing inorganic material, and the thickness of the coating layer is 5-50 nm. The general formula of the single-crystal lithium-rich manganese-based cathode material is Li. 1+x Ni a Co b Mn c M y Q z O2, where a+b+c=1, 0.2≤a≤0.5, 0≤b≤0.1, 0.08≤x≤0.28, 0<y≤0.03, 0<z≤0.04, M and Q are doping elements, and M exists in the coating layer. M is selected from at least one of F, P, B, and S, and Q is selected from at least one of Zr, Al, W, Mg, Ti, V, and Mo.

[0048] This application involves coating the surface of single-crystal lithium-rich manganese-based particles with a layer of lithium-containing inorganic material doped with element M. The doping of element M forms a coating layer with high ionic conductivity and chemical stability. This coating layer effectively suppresses contact with the electrolyte under high voltage and reduces the generation of interfacial side reactions, thereby significantly reducing the rate of increase in DC internal resistance and suppressing gas escape under high-temperature conditions. The doping of element Q in the single-crystal lithium-rich manganese-based particles further stabilizes the crystal structure, enhancing structural stability and cycle stability under high nickel content. Simultaneously, the regulation of x, y, z and composition enables the material to achieve high specific capacity and low impedance growth while improving the initial charge-discharge efficiency and cycle stability of lithium-ion batteries.

[0049] It needs to be explained that Li 1+x Ni a Co b Mn c M y Q z O2 is the general formula for the elemental composition of a single-crystal lithium-rich manganese-based cathode material. The single-crystal lithium-rich manganese-based cathode material consists of two parts, an inner and an outer part, and the elemental composition of the two parts as a whole is the general formula above.

[0050] In some specific embodiments, the coating thickness is any value or a range between 5nm, 10nm, 15nm, 20nm, 30nm, 40nm, and 50nm; in the general formula of the single-crystal lithium-rich manganese-based cathode material, a is any value or a range between 0.2, 0.3, 0.4, and 0.5; b is any value or a range between 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, and 0.1; and x is 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, and 0.2. 2. Any value among 0.24, 0.26, and 0.28, or a range between any two; y is any value among 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, 0.022, 0.024, 0.026, 0.028, and 0.03, or a range between any two; z is any value among 0.01, 0.012, 0.014, 0.016, 0.018, 0.02, 0.022, 0.024, 0.026, 0.028, 0.03, 0.032, 0.034, 0.036, 0.038, and 0.04, or a range between any two.

[0051] In some embodiments, the particle size of the monocrystalline lithium-rich manganese-based cathode material is 2-6 μm. Controlling the particle size of the monocrystalline lithium-rich manganese-based cathode material can further improve interfacial stability. Too small a particle size leads to an excessively large particle surface area, exacerbating side reactions, while too large a particle size reduces the integrity and uniformity of the coating layer on the surface of the monocrystalline lithium-rich manganese-based particles. A suitable particle size can further improve the volumetric energy density and ensure the integrity and uniformity of the coating layer on the monocrystalline lithium-rich manganese-based particles, thereby improving the electrochemical performance and cycle stability of the lithium-ion battery. Specifically, the particle size of the monocrystalline lithium-rich manganese-based cathode material is any value from 2 μm, 3 μm, 4 μm, 5 μm, and 6 μm, or a range between any two.

[0052] To further improve the electrochemical performance and cycle stability of monocrystalline lithium-rich manganese-based cathode materials, in some preferred embodiments, the general formula of the monocrystalline lithium-rich manganese-based cathode material is 0.1≤x≤0.25, 0<y≤0.02, 0<z≤0.02; Q is selected from at least one of Zr, Al, W, Ti, and V; and the thickness of the coating layer is 5~20nm.

[0053] To further enhance the formation of a single-crystal lithium-rich manganese-based cathode material by combining the single-crystal lithium-rich manganese-based particles with the coating layer, and to maintain the lattice stability of the single-crystal particles under high voltage, lithium-containing inorganic materials are used as the coating layer to form a dense and stable interfacial barrier, thereby significantly reducing interfacial side reactions. In some preferred embodiments, the chemical formula of the single-crystal lithium-rich manganese-based particles is Li.1.2 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.08 Ni 0.2 Co 0.1 Mn 0.7 F 0.02 Al 0.005 O2, Li 1.25 Ni 0.4 Co 0.08 Mn 0.5 2F 0.01 Al 0.01 O2, Li 1.1 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.28 Ni 0.5 Co 0.05 Mn 0.45 F 0.005 Al 0.02 At least one of O2; the lithium-containing inorganic substance contains lithium element and also contains at least one selected from ZrO2, Al2O3, WO3, MgO, TiO2, V2O5, MoO3, AlF3, TiF2, ZrF2, MgF2, AlPO4, and AlBO3.

[0054] In a second typical embodiment of this application, a method for preparing a single-crystal lithium-rich manganese-based cathode material is provided, the method comprising:

[0055] Step S1: Prepare the precursor by mixing nickel source, cobalt source, manganese source and dopant element Q source to form the precursor;

[0056] Step S2: The precursor and lithium source are mixed in stoichiometric ratio to obtain a mixture, and the mixture is subjected to a first sintering to obtain a first sintered product.

[0057] Step S3: The first sintered product is mixed with the dopant element M source for a second sintering, so that the dopant element M source is doped onto the lithium-containing inorganic coating layer formed on the surface of the first sintered product to obtain the second sintered product. The second sintered product is then crushed and sieved to obtain a single-crystal lithium-rich manganese-based cathode material.

[0058] In this application, a precursor containing nickel, cobalt, manganese, and a dopant element Q source is first prepared, then mixed with a lithium source for a first sintering to form single-crystal lithium-rich manganese-based particles. Subsequently, a dopant element M source is subjected to a second sintering, causing the dopant element M to be doped onto the surface of the first sintered product to form a lithium-containing inorganic coating layer, resulting in a second sintered product. The second sintered product is then crushed and sieved to obtain a single-crystal lithium-rich manganese-based cathode material. This lithium-containing inorganic coating layer not only tightly bonds with the interface of the single-crystal lithium-rich manganese-based particles, but the F, P, and B elements doped in it can effectively stabilize lattice oxygen, inhibit electrolyte oxidation and decomposition, and reduce interface impedance. This improves the initial coulombic efficiency of the lithium-ion battery while reducing gas generation and DC internal resistance growth, thereby enhancing the cycle life of the lithium-rich manganese-based cathode material.

[0059] In some embodiments, step S1, the precursor preparation method includes: step S11, mixing a nickel source, a cobalt source, a manganese source, and a dopant element Q source to obtain a mixed metal salt; and step S12, mixing the mixed metal salt, a precipitant, and a complexing agent to prepare the precursor. By dissolving the nickel source, cobalt source, manganese source, and dopant element Q source together to form a uniform mixed metal salt solution, and introducing a precipitant and a complexing agent during the precipitation process to conduct a co-precipitation reaction, the dopant element Q is uniformly dispersed in the precursor and participates in the formation of the crystal lattice. This lays a good foundation for the formation of stable doped, well-grained single-crystal lithium-rich manganese-based particles in the subsequent first sintering process, thereby achieving a simultaneous improvement in the electrochemical performance and cycle life of the single-crystal lithium-rich manganese-based cathode material.

[0060] In some embodiments, the temperature of the first sintering is 850~1000℃, the time of the first sintering is 8-20h, and the heating rate of the first sintering is 2~10℃ / min. The first sintering enables the precursor and lithium source to be mixed to generate a structurally complete first sintered product, avoiding lattice defects and excessive surface activity in the first sintered product due to insufficient or excessive sintering, thus laying a good structural foundation for the subsequent second sintering to form the coating layer. Specifically, the temperature of the first sintering is any value or a range between any two of 850℃, 860℃, 870℃, 880℃, 890℃, 900℃, 910℃, 920℃, 930℃, 940℃, 950℃, 960℃, 970℃, 980℃, 990℃, and 1000℃; the time of the first sintering is any value or a range between any two of 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, and 20h; and the heating rate of the first sintering is any value or a range between any two of 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, and 10℃ / min.

[0061] In some embodiments, the second sintering temperature is 300~700℃, the second sintering time is 4~10h, and the second sintering heating rate is 2~10℃ / min. By controlling the temperature, time, and heating rate of the second sintering, the dopant element M can further form a coating layer in the second sintering, coating the surface of the first sintered product. This avoids instability of the coating layer structure due to excessively high sintering temperature or excessively long sintering time. This coating layer can further suppress the contact between the positive electrode active material and the electrolyte, reduce the generation of interfacial side reactions, and thus improve the electrochemical stability of the single-crystal lithium-rich manganese-based positive electrode material. Specifically, the temperature of the second sintering is any value or a range between any two of 300℃, 350℃, 400℃, 450℃, 500℃, 550℃, 600℃, 650℃, and 700℃; the time of the second sintering is any value or a range between any two of 4h, 5h, 6h, 7h, 8h, 9h, and 10h; and the heating rate of the second sintering is any value or a range between any two of 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, and 10℃ / min.

[0062] In order to further prevent the material from being oxidized during the first sintering process and to ensure that the chemical composition and properties of the sintered body are not damaged, in some specific embodiments, the first sintering is carried out under a protective atmosphere, which includes, but is not limited to, at least one of nitrogen, argon and helium.

[0063] In some embodiments, the second sintering is carried out in a mixed atmosphere, which is a mixture of an inert gas and a reducing gas. The inert gas is selected from at least one of helium and argon, and the reducing gas is selected from at least one of hydrogen, carbon monoxide, and ammonia. The volume of the reducing gas accounts for 3% to 5% of the volume of the mixed atmosphere. The mixed atmosphere of inert and reducing gases used in the second sintering further enables the dopant element M to partially reduce the surface of the single-crystal lithium-rich manganese-based particles, forming a stable coating layer on the surface of the particles, and regulating the oxygen vacancies on the surface of the particles, thereby improving the conductivity and ion mobility of the single-crystal lithium-rich manganese-based cathode material. Specifically, the volume of the reducing gas accounts for any value from 3%, 4%, and 5% of the volume of the mixed atmosphere, or any value between two of these values.

[0064] In some embodiments, in step S2, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, or lithium nitrate; in step S3, the dopant element M source is selected from at least one of lithium fluoride, ammonium dihydrogen phosphate, boron oxide, aluminum trifluoride, lithium manganese borate, and lithium vanadium phosphate. By limiting the lithium source, lithium can be uniformly diffused during the first sintering process, thereby forming structurally complete single-crystal lithium-rich manganese-based particles. Furthermore, by further limiting the dopant element M source, a stable and dense lithium-containing inorganic coating layer can be formed during the second sintering process, thereby significantly reducing the increase in DC internal resistance caused by interfacial side reactions and synergistically improving the electrochemical performance and cycle stability of the lithium-ion battery.

[0065] To further enable the metal components to coexist in the solution system during the precursor preparation stage, thereby achieving uniform mixing and precipitation of the metals in the co-precipitation reaction, and significantly improving the lattice integrity of the single-crystal lithium-rich manganese-based cathode material, thus providing a stable foundation for the subsequent coating layer formation, in some embodiments, in step S11, the nickel source is a soluble nickel salt selected from at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate; the cobalt source is a soluble cobalt salt selected from at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; the manganese source is a soluble manganese salt selected from at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate; and the dopant element Q source is at least one of a sulfate, nitrate, chloride, or oxide containing the dopant element Q.

[0066] In some embodiments, step S12 further includes mixing the mixed metal salt solution, precipitant and complexing agent to carry out a co-precipitation reaction, followed by drying to obtain a precursor. By first carrying out a co-precipitation reaction of the mixed metal salt solution, precipitant and complexing agent, the precursor can be further mixed to prepare a precursor, thereby improving the crystallinity and morphological consistency of the precursor, and thus enabling the precursor to maintain structural integrity and stability in the first sintering.

[0067] In some embodiments, the pH value of the coprecipitation reaction is 10.5-12, the temperature of the coprecipitation reaction is 40-70°C, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate, and the complexing agent is selected from at least one of ammonia, citric acid, and ethylenediaminetetraacetic acid. By controlling the pH value, reaction temperature, and the precipitant and complexing agent during the precipitation reaction, problems such as coating layer detachment or uneven coating caused by precursor agglomeration, elemental segregation, or lattice defects are further avoided, thereby ensuring the structural stability of the single-crystal lithium-rich manganese-based cathode material, improving the initial coulombic efficiency of lithium-ion batteries, slowing down the growth of DC internal resistance, and improving battery cycle life.

[0068] In a third typical embodiment of this application, a lithium-ion battery is provided, which includes a positive electrode sheet, which includes a monocrystalline lithium-rich manganese-based positive electrode material provided in the first typical embodiment or a monocrystalline lithium-rich manganese-based positive electrode material prepared by the preparation method provided in the second typical embodiment.

[0069] This application also provides a lithium-ion battery in which the positive electrode uses a lithium-rich manganese-based positive electrode material with a single-crystal structure and a lithium-containing inorganic coating layer on the surface. This material significantly reduces interfacial side reactions while improving the initial coulombic efficiency. The coating layer is composed of lithium-containing inorganic materials with elements such as F, P, and B, and its thickness is controllable. It can effectively suppress the oxidative decomposition of the electrolyte under high voltage, thereby suppressing the continuous increase of DC internal resistance and reducing gas generation during high-temperature storage or cycling. The single-crystal lithium-rich manganese-based particle structure avoids the intergranular cracking problem that is prone to occur in secondary spherical particles during cycling, improves the mechanical stability of the material, and enables the lithium-ion battery to maintain high energy density while having better cycle stability and safety. It is suitable for power battery systems with high requirements for energy density and safety.

[0070] The beneficial effects of this application will be further illustrated below with reference to embodiments and comparative examples.

[0071] Example 1

[0072] This embodiment provides a method for preparing a single-crystal lithium-rich manganese-based cathode material, the method comprising:

[0073] (1) According to Li 1.2 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2 stoichiometrically weighed nickel source (nickel chloride), cobalt source (cobalt nitrate), manganese source (manganese chloride), and dopant element Q source (alumina) to obtain a mixed metal salt. The mixed metal salt, precipitant (NaOH solution, concentration 10 mol / L), and complexing agent (ammonia water, concentration 6 mol / L) were mixed and added to a reaction vessel for stirring and co-precipitation reaction to obtain the precursor. The pH value of the co-precipitation reaction was 11, and the temperature of the co-precipitation reaction was 50℃.

[0074] (2) The lithium source (lithium carbonate) and the precursor are mixed according to the stoichiometric ratio to obtain a mixture. The mixture is heated to 900°C under a nitrogen protective atmosphere at a heating rate of 5°C / min for the first sintering. The first sintered product is obtained after sintering for 12 hours.

[0075] (3) The first sintering product and the doping element M source (lithium fluoride) are mixed in a mixed atmosphere and heated to 500°C at a heating rate of 5°C / min for the second sintering. After sintering for 6 hours, the second sintering product is obtained. The second sintering product is crushed and sieved to obtain a single crystal lithium-rich manganese-based cathode material. The mixed atmosphere is a mixture of argon and hydrogen, with hydrogen accounting for 4% of the mixed atmosphere.

[0076] Example 2

[0077] The difference between this embodiment and embodiment 1 is that, in adjustment step (1), according to Li 1.08 Ni 0.2 Co 0.1 Mn 0.7 F 0.02 Al 0.005 Weigh the raw materials according to the stoichiometric ratio of O2.

[0078] Example 3

[0079] The difference between this embodiment and embodiment 1 is that, in adjustment step (1), according to Li 1.28 Ni 0.5 Co 0.05 Mn 0.45 F 0.005 Al 0.02 Weigh the raw materials according to the stoichiometric ratio of O2.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that, in adjustment step (1), according to Li 1.1 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 Weigh the raw materials according to the stoichiometric ratio of O2.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that, in adjustment step (1), according to Li 1.25 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 Weigh the raw materials according to the stoichiometric ratio of O2.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that the doping element Q source (Ti) is adjusted in step (1).

[0086] Example 7

[0087] The difference between this embodiment and embodiment 1 is that the doping element Q source (Zr) is adjusted in step (1).

[0088] Example 8

[0089] The difference between this embodiment and embodiment 1 is that the doping element Q source (Mg) is adjusted in step (1).

[0090] Example 9

[0091] The difference between this embodiment and embodiment 1 is that in step (3), the dopant element M source (ammonium dihydrogen phosphate) is adjusted.

[0092] Example 10

[0093] The difference between this embodiment and embodiment 1 is that in step (3), the doping element M source (boron oxide) is adjusted.

[0094] Example 11

[0095] The difference between this embodiment and embodiment 1 is that in the adjustment step (2), the temperature of the first sintering is 850°C and the time of the first sintering is 20h.

[0096] Example 12

[0097] The difference between this embodiment and embodiment 1 is that in the adjustment step (2), the temperature of the first sintering is 1000℃ and the time of the first sintering is 8h.

[0098] Example 13

[0099] Compared with Example 1, the difference in this embodiment is that in the adjustment step (3), the temperature of the second sintering is 300°C, the time of the second sintering is 10h, and the mixed atmosphere is a mixture of helium and carbon monoxide, with carbon monoxide accounting for 3% of the mixed atmosphere.

[0100] Example 14

[0101] Compared with Example 1, the difference in this embodiment is that in the adjustment step (3), the temperature of the second sintering is 700°C, the time of the second sintering is 4h, and the mixed atmosphere is a mixture of argon and carbon monoxide, with carbon monoxide accounting for 5% of the mixed atmosphere.

[0102] Example 15

[0103] The difference between this embodiment and embodiment 1 is that in adjustment step (2), the temperature of the first sintering is 800°C and the time of the first sintering is 25h.

[0104] Example 16

[0105] The difference between this embodiment and embodiment 1 is that in the adjustment step (2), the temperature of the first sintering is 1100℃ and the time of the first sintering is 5h.

[0106] Example 17

[0107] The difference between this embodiment and embodiment 1 is that, in step (3), the temperature of the second sintering is 250°C and the time of the second sintering is 10h.

[0108] Example 18

[0109] The difference between this embodiment and embodiment 1 is that in step (3), the temperature of the second sintering is 750°C and the time of the second sintering is 4 hours.

[0110] Example 19

[0111] Compared with Example 1, this embodiment differs in that the lithium source (lithium carbonate), precursor and dopant element M source (lithium fluoride) in steps (2) and (3) are mixed and then sintered once. The sintering temperature is 680°C and the sintering time is 8h under an argon atmosphere.

[0112] Comparative Example 1

[0113] The difference between this comparative example and Example 1 is that no dopant element Q is added in step (1).

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 1 is that no doping element M is added in step (3), and the first sintering product is a single-crystal lithium-rich manganese-based cathode material.

[0116] Comparative Example 3

[0117] The difference between this comparative example and Example 1 is that, in step (1), Li1Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.0 1O2.

[0118] Experimental Example 1

[0119] (1) The single-crystal lithium-rich manganese-based cathode material, conductive agent (SuperP), and binder (polyvinylidene fluoride (PVDF)) prepared in the above examples and comparative examples are mixed in a mass ratio of 90:5:5 to obtain a cathode slurry with a solid content of 52%. The cathode slurry is coated on an aluminum foil current collector and dried to obtain a cathode electrolyte membrane. After cold pressing and slicing, a cathode electrode sheet is obtained.

[0120] (2) Negative electrode sheet: The mass ratio of graphite (active material), sodium carboxymethyl cellulose (CMC) (thickener), and binder (styrene-butadiene rubber SBR) is 95.5:2.5:2. CMC is pre-dissolved in deionized water, graphite powder is added and dispersed by high-speed stirring, and finally SBR emulsion is added and mixed slowly to obtain a negative electrode slurry with a solid content of 51.8 wt%. The slurry is uniformly coated on copper foil (negative electrode current collector), dried in an oven to remove moisture, and then compacted to the target density of the electrode sheet by a roller press. After cutting, the negative electrode sheet is obtained.

[0121] (3) The diaphragm is a ceramic-coated PE diaphragm; the electrolyte is FLMCB-02 (purchased from Guangzhou Tinci Advanced Materials Co., Ltd.).

[0122] (4) Assemble the positive electrode, negative electrode, separator and electrolyte into a lithium-ion battery.

[0123] The prepared lithium-ion battery was subjected to electrochemical performance testing under the following conditions:

[0124] (1) Routine charge and discharge test: 25℃±2℃, 0.1C constant current charging to 4.55V, constant voltage charging at 4.55V until the current drops to 0.02C; constant current discharge at 0.1C to 2.5V.

[0125] (2) Rate test: At 25℃±2℃, fully charge according to the above test procedure (0.1C to 4.55V, constant voltage to 0.02C), and discharge at different rates of 0.2C, 0.5C, 1C, 2C, and 3C to 2.5V.

[0126] (3) Cyclic test: 25±2℃, 1C constant current charge to 4.55V, constant voltage to 0.02C, stand for 10 minutes, 1C constant current discharge to 2.5V, stand for 10 minutes, when the discharge capacity is lower than 80% of the initial capacity, stop the test.

[0127] The test results are shown in Table 1.

[0128] Table 1

[0129]

[0130]

[0131] Comparing Examples 1-19 with Comparative Examples 1-3, it can be seen that the coating layer formed on the surface of the single-crystal lithium-rich manganese-based cathode material prepared in Examples 1-19 can effectively isolate the direct contact between the electrolyte and the single-crystal lithium-rich manganese-based particles under high voltage, effectively suppressing interfacial side reactions and transition metal dissolution. Furthermore, the appropriate thickness of the coating layer and the appropriate ratio of each component in the lithium-rich manganese-based cathode material can reduce the DC resistance of the battery during cycling. At the same time, introducing at least one stable doping element of Zr, Al, W, Mg, Ti, V, and Mo into the lithium-rich manganese-based cathode material and adding excess lithium for lithium replenishment can effectively reduce lithium loss. Meanwhile, the reasonable ratio of each component in the single-crystal lithium-rich manganese-based cathode material can improve the coulombic efficiency during the first charge and discharge process of the lithium-ion battery and the cycle stability of the lithium-ion battery. In Comparative Example 1, the lack of doping elements resulted in poor lattice stability of the single-crystal lithium-rich manganese-based cathode material, leading to poor cycle stability. In Comparative Example 2, the lack of doping element M resulted in the absence of a coating layer with high ionic conductivity and chemical stability, resulting in a low specific capacity of the lithium-ion battery at 1C. In Comparative Example 3, the lack of lithium replenishment resulted in low specific capacity and cycle stability of the lithium-ion battery.

[0132] Furthermore, by optimizing the process parameters at each stage of the preparation process, especially the first and second sintering stages, the coulombic efficiency during the first charge-discharge process of lithium-ion batteries and the cycle stability of lithium-ion batteries can be further improved.

[0133] Comparing Examples 1-14 with Examples 15-16, it can be seen that the suitable temperature and time for the first sintering in Examples 1-14 can enable the precursor and lithium source to mix and generate a structurally complete first sintered product, avoiding insufficient or excessive sintering that could lead to lattice defects and excessively high surface activity in the first sintered product.

[0134] Comparing Examples 1-14 and Examples 17-18, it can be seen that the suitable second sintering temperature and time in Examples 1-14 enable the dopant element M to form a coating layer in the second sintering, coating the surface of the first sintering product. This avoids the instability of the coating layer structure due to excessively high sintering temperature or excessively long sintering time. Furthermore, this coating layer can further suppress the contact between the positive electrode active material and the electrolyte, reduce the generation of interfacial side reactions, and thus improve the electrochemical stability of the single-crystal lithium-rich manganese-based positive electrode material.

[0135] Compared with Example 19, Examples 1-14 show that the first and second sintering of the mixture in Examples 1-14 is beneficial to form structurally stable single crystal particles through high-temperature sintering, reduce interfacial side reactions with electrolyte, improve the coulombic efficiency of lithium-ion batteries during the first charge and discharge process, and have excellent cycle stability.

[0136] Figure 1 A SEM image of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application is shown. Figure 1 It can be seen that the prepared material has a typical single crystal morphology, with good particle dispersion and uniformity, and the coating layer is uniform, thus proving the successful preparation of the surface coating of single crystal lithium-rich manganese-based cathode material at the microscale.

[0137] Figure 2 The charge-discharge curves of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application are shown at 0.1C and 1C rates. Figure 2 It can be seen that the prepared single-crystal lithium-rich manganese-based cathode material has a specific capacity of 168.78 mAh / g and 162.39 mAh / g at 0.1C and 1C charge / discharge rates, respectively, and has a high charge / discharge capacity and a high first-cycle coulombic efficiency of 95.84%.

[0138] Figure 3 The cycling retention curve of the single-crystal lithium-rich manganese-based cathode material prepared according to Example 1 of this application after 500 cycles at 1C is shown. Figure 3 It can be seen that the single-crystal lithium-rich manganese-based cathode material prepared in Example 1 has an overall room temperature cycle count of more than 500 cycles and a cycle retention rate of more than 94% under 1C charging and 1C discharging conditions, demonstrating excellent cycle performance.

[0139] As can be seen from the above description, the embodiments of this application achieve the following technical effects:

[0140] This application provides a single-crystal lithium-rich manganese-based cathode material. The coating layer formed on the surface of the single-crystal lithium-rich manganese-based particles can effectively isolate the direct contact between the electrolyte and the single-crystal lithium-rich manganese-based particles under high voltage, further effectively suppressing interfacial side reactions and transition metal dissolution. Furthermore, by controlling the thickness of the coating layer and the content of each component in the lithium-rich manganese-based cathode material, the DC resistance (DCR) of the battery during cycling is reduced. At the same time, introducing at least one stable doping element of Zr, Al, W, Mg, Ti, V, and Mo into the lithium-rich manganese-based cathode material and adding excess lithium for lithium replenishment can effectively reduce lithium loss. Meanwhile, the control of x, y, z and composition can improve the coulombic efficiency during the first charge and discharge process of the lithium-ion battery and the cycle stability of the lithium-ion battery.

[0141] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A single-crystal lithium-rich manganese-based cathode material, characterized in that, The monocrystalline lithium-rich manganese-based cathode material comprises monocrystalline lithium-rich manganese-based particles and a coating layer covering the surface of the monocrystalline lithium-rich manganese-based particles. The coating layer is made of lithium-containing inorganic material, and the thickness of the coating layer is 5-50 nm. The general formula of the monocrystalline lithium-rich manganese-based cathode material is Li. 1+x Ni a Co b Mn c M y Q z O2, where a+b+c=1, 0.2≤a≤0.5, 0≤b≤0.1, 0.08≤x≤0.28, 0<y≤0.03, 0<z≤0.04, M and Q are doping elements, and M exists in the coating layer. M is selected from at least one of F, P, and B, and Q is selected from at least one of Zr, Al, W, Mg, Ti, V, and Mo.

2. The single-crystal lithium-rich manganese-based cathode material according to claim 1, characterized in that, The particle size of the single-crystal lithium-rich manganese-based cathode material is 2~6μm; Preferably, in the general formula of the single-crystal lithium-rich manganese-based cathode material, 0.1≤x≤0.25, 0<y≤0.02, and 0<z≤0.02; Preferably, Q is selected from at least one of Zr, Al, W, Ti, and V; Preferably, the thickness of the coating layer is 5~20nm.

3. The single-crystal lithium-rich manganese-based cathode material according to claim 1 or 2, characterized in that, The lithium-containing inorganic material contains lithium and also contains at least one selected from ZrO2, Al2O3, WO3, MgO, TiO2, V2O5, MoO3, AlF3, TiF2, ZrF2, MgF2, AlPO4, and AlBO3. And / or, the chemical formula of the single-crystal lithium-rich manganese-based particles is selected from Li 1.2 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.08 Ni 0.2 Co 0.1 Mn 0.7 F 0.02 Al 0.005 O2, Li 1.25 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.1 Ni 0.4 Co 0.08 Mn 0.52 F 0.01 Al 0.01 O2, Li 1.28 Ni 0.5 Co 0.05 Mn 0.45 F 0.005 Al 0.02 At least one of O2.

4. The method for preparing the single-crystal lithium-rich manganese-based cathode material according to any one of claims 1 to 3, characterized in that, The preparation method includes: Step S1: Prepare the precursor by mixing nickel source, cobalt source, manganese source and dopant element Q source to form the precursor; Step S2: The precursor and lithium source are mixed in stoichiometric ratio to obtain a mixture, and the mixture is subjected to a first sintering to obtain a first sintered product. Step S3: The first sintered product is mixed with the dopant element M source for a second sintering, so that the dopant element M is doped on the surface of the first sintered product to form a lithium-containing inorganic coating layer, and the second sintered product is obtained; the second sintered product is crushed and sieved to obtain the single crystal lithium-rich manganese-based cathode material.

5. The preparation method according to claim 4, characterized in that, In step S1, the method for preparing the precursor includes: Step S11: Mix the nickel source, the cobalt source, the manganese source and the doping element Q source to obtain a mixed metal salt; Step S12: The precursor is prepared by mixing the mixed metal salt, precipitant and complexing agent.

6. The preparation method according to claim 4, characterized in that, The temperature of the first sintering is 850~1000℃, the time of the first sintering is 8-20h, and the heating rate of the first sintering is 2~10℃ / min, preferably 2~5℃ / min; And / or, the temperature of the second sintering is 300~700℃, the time of the second sintering is 4~10h, and the heating rate of the second sintering is 2~10℃ / min; And / or, the first sintering is carried out under a protective atmosphere selected from at least one of nitrogen, argon, and helium; And / or, the second sintering is carried out in a mixed atmosphere, which is a mixture of an inert gas and a reducing gas; Preferably, the inert gas is selected from at least one of helium and argon, and the reducing gas is selected from at least one of hydrogen, carbon monoxide, and ammonia, wherein the volume of the reducing gas accounts for 3% to 5% of the volume of the mixed atmosphere.

7. The preparation method according to any one of claims 4 to 6, characterized in that, In step S2, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, or lithium nitrate. And / or, in step S3, the dopant element M source is selected from at least one of lithium fluoride, ammonium dihydrogen phosphate, boron oxide, aluminum trifluoride, lithium manganese borate, and lithium vanadium phosphate.

8. The preparation method according to any one of claims 4 to 7, characterized in that, In step S11, the nickel source is a soluble nickel salt, which is selected from at least one of nickel sulfate, nickel nitrate, nickel chloride, and nickel acetate. And / or, the cobalt source is a soluble cobalt salt, wherein the soluble cobalt salt is selected from at least one of cobalt sulfate, cobalt nitrate, cobalt chloride, and cobalt acetate; And / or, the manganese source is a soluble manganese salt, which is selected from at least one of manganese sulfate, manganese nitrate, manganese chloride, and manganese acetate; And / or, the dopant element Q source is at least one of sulfate, nitrate, chloride or oxide containing the dopant element Q.

9. The preparation method according to any one of claims 4 to 8, characterized in that, Step S12 further includes mixing the mixed metal salt solution, precipitant and complexing agent to carry out a co-precipitation reaction, followed by drying to obtain the precursor; And / or, the pH value of the coprecipitation reaction is 10.5~12; And / or, the temperature of the coprecipitation reaction is 40~70℃; And / or, the precipitant is selected from at least one of sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate; And / or, the complexing agent is selected from at least one of ammonia, citric acid, and ethylenediaminetetraacetic acid.

10. A lithium-ion battery, characterized in that, The lithium-ion battery includes a positive electrode sheet, which comprises a monocrystalline lithium-rich manganese-based positive electrode material according to any one of claims 1 to 3 or a monocrystalline lithium-rich manganese-based positive electrode material prepared by any one of claims 4 to 9.